use of Kahoot! in teaching grammar: A case study of Politeknik Kota Bharu students - Nik Nur Fathiha Nik Din; Nurul Aini Othman (Pejabat Karang Mengarang UPSI, 2023)
The purpose of this study was to investigate how students felt about using Kahoot! in grammar classrooms. This study used an exploratory qualitative case study approach with written structured interviews and classroom observations as the primary data collection methods. In order to collect the data and accomplish the objectives, class observations were conducted with a class of 24 students. The observation checklist and field notes were used during the class observations to record the findings. Six students then participated in written structured interview sessions. The written structured interview was examined, and field notes were subjected to content analysis. The results show that using Kahoot! in grammar lessons has a beneficial impact on students' interest, motivation, and classroom behavior. The gamification benefits also decreased students' anxiety when learning grammar and enhanced their intrinsic motivation to learn English. According to the findings, this study is important because it will give English lecturers at Politeknik Kota Bharu, prospective lecturers, curriculum designers, and the Higher Ministry of Education a platform to discuss some of the challenges students encounter when learning grammar and to adjust as needed. Also, it will support teachers in developing better teaching methods for students that struggle in the classroom. For the students, this study is anticipated to increase their motivation to learn English, particularly in grammar, which is typically considered dull and tedious. As a result, program planners may benefit from the additional teaching methods it offers.